Identity and typification of Commelina vilavelhensis (Commelinaceae), and typification of C. robusta and C. scabrata - Hassemer, Gustavo; Ferreira, João Paulo Ramos; Funez, Luís Adriano; Aona, Lidyanne Yuriko Saleme (Phytotaxa, 2016)
With this contribution we designate a lectotype for the name Commelina vilavelhensis, and present evidence for the synonymisation of this name under C. obliqua. We also designate here lectotypes for the names C. robusta and C. scabrata, other synonyms of C. obliqua, and discuss the taxonomic and nomenclatural situation of the name Heterocarpus obliquus. Furthermore, we present evidence that the lectotype of C. obliqua originated from plants cultivated in Paris, France and not in Uppsala, Sweden as currently accepted. We also provide here the first identification key to the eight species of Commelina that occur in the South region of Brazil.